Functional Optical Zone After Small-Incision Lenticule Extraction as Stratified by Attempted Correction and Optical Zone. Issue 9 (September 2018) - Fu, Dan; Wang, Lin; Zhou, Xingtao; Yu, Zhiqiang
Abstract : Purpose: To compare the functional optical zone (OZ) with different levels of myopia and different OZ groups after small-incision lenticule extraction. Methods: This retrospective study included 249 patients (120 men) after small-incision lenticule extraction correction. We grouped participants according to attempted correction [low: spherical equivalent (SE) > −3.0 D; moderate: −6.0 D ≥ SE ≥ −3.0 D; high: SE ≥ −6.0 D] and planned functional optical zone (PFOZ) (OZ-1: PFOZ ⩽ 6.3 mm; OZ-2: 6.3 mm < PFOZ ⩽ 6.5; OZ-3: PFOZ > 6.5 mm), and we compared the achieved functional optical zone (AFOZ) and total corneal aberration, using Scheimpflug imaging, 1 month postoperatively. Correlations between corneal aberration and AFOZ were analyzed. Results: The AFOZ was smaller than the PFOZ in all 3 refraction groups (reduction: low, 0.78 ± 0.72 mm; moderate, 1.22 ± 0.60 mm; and high: 1.49 ± 0.58 mm, P < 0.001). There was no difference in the AFOZ among the 3 OZ groups. Total corneal aberration increased more in the high myopia group (total higher-order aberration, coma, and spherical aberration, P < 0.001), which also correlated with the AFOZ. Conclusions: The discrepancy between the AFOZ and PFOZ increased with greater attempted correction. Attempted correction and AFOZ influence corneal aberration.